2008
DOI: 10.1002/ar.20651
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Hypertrophy in Offspring of Subtotally Nephrectomized Ewes

Abstract: We have shown that fetuses whose mothers underwent subtotal nephrectomy (STNx) before pregnancy had high urine flow rates and sodium excretions, but lower hematocrits, plasma chloride, and plasma renin levels compared with controls. To see if these functional differences in utero persist after birth and are the result of altered renal development, we studied 8 lambs born to STNx mothers (STNxL) and 10 controls (ConL) in the second week of life. These lambs were of similar body weights, nose-rump lengths and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…It was concluded that these fetuses were exposed throughout pregnancy to an increased transplacental net flux of salt and water 7,8 and that this led to chronic suppression of renin secretion from the fetal kidneys. In contrast, by the second week after birth, the lambs were euvolaemic 4 . In particular, all the parameters that were used as indicators of increased transplacental fluid flux (baseline urine flow and sodium excretion rate, proximal tubular sodium handling, haematocrit, plasma chloride and plasma renin level) were similar to control lambs 4 …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It was concluded that these fetuses were exposed throughout pregnancy to an increased transplacental net flux of salt and water 7,8 and that this led to chronic suppression of renin secretion from the fetal kidneys. In contrast, by the second week after birth, the lambs were euvolaemic 4 . In particular, all the parameters that were used as indicators of increased transplacental fluid flux (baseline urine flow and sodium excretion rate, proximal tubular sodium handling, haematocrit, plasma chloride and plasma renin level) were similar to control lambs 4 …”
Section: Introductionmentioning
confidence: 85%
“…We have undertaken a number of studies into the effects of maternal renal dysfunction on renal development and function 2–6 . These experiments were in fetuses, newborn and 6‐month‐old lambs conceived and carried by ewes in which two‐thirds of their renal mass had been removed (by unilateral nephrectomy and partial infarction of the remaining kidney; STNx) at least 2 months before mating.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of ANG- (1)(2)(3)(4)(5)(6)(7). ANG-(1-7) was obtained from Bachem BioScience (King of Prussia, PA).…”
Section: Animalsmentioning
confidence: 99%
“…SINCE ANTENATAL STEROID TREATMENT became the standard of care for enhancing fetal lung maturation in pregnancies threatened by premature labor between 24 and 34 wk of gestation, the use of corticosteroid therapy in the United States has increased from Ͻ15% of eligible pregnancies in 1990 to Ͼ75% in 1995 (1,3). However, clinical epidemiological studies show an association between antenatal glucocorticoid administration and altered vascular function (7,46), suggesting that exposure to excess glucocorticoids in the prenatal period may have untoward consequences in adult offspring.…”
mentioning
confidence: 99%
“…2 Coupled with these findings are observations from animal studies that impaired maternal renal function during pregnancy leads to hyperfiltration by the fetus and neonate and to glomerulomegaly. 76 From early adult life, albuminuria is pervasive in Indigenous communities. 77 Therefore, as part of a cycle, there is evidence of renal damage in Aboriginal women of childbearing age.…”
Section: Role Of the Renal Ras In Adult Life In The Pathogenesis Of Cmentioning
confidence: 99%